Common Errors in English Aphasic Discourse - Kotys, Olena; Bondar, Tetiana; Servatovych , Viktoria (East European Journal of Psycholinguistics, 2022)
The article generalizes the results of research directed onto singling out the common errors in speech of aphasic patients. Aphasia is characterized by partial or complete loss of speech and is caused by damage in the language areas (Broca’s and Wernicke’s areas). A lesion in the middle part of the patient’s left frontal lobe results in Broca’s aphasia and the damage to the left posterior superior temporal gyrus is referred to as Wernicke’s aphasia. The major causes of aphasia are strokes, cortical vein thrombosis, traumas of skull and brain, brain infections, tumors, etc. The research is based on the language-in-use descriptive approach to discourse analysis and presents an investigation of 40 documentary video recordings of aphasic patients’ speech (free narration and dialogues); the overall duration of the recordings is 180 minutes. The inclusion criterion was aphasia of any type in adulthood. All the patients are English-speaking people (English being their native language) recovering from aphasia.  The analysis was done according to the following criteria: intelligibility, coherence, cohesion, grammatical structure of utterances, prosody and intonation, thus combining formalist (or structuralist) and functionalist research paradigms. The research has shown that the most common errors that aphasic patients make when speaking are as follows: syntactic errors, articulatory errors, lexical misuse and slow speech rate. Syntactic and articulatory errors prevail (55% and 50% of all the studied cases respectively), whereas 37.5% of the speakers demonstrated slow speech rate. The speech of 75% of people with aphasia is incoherent. The patients’ verbal performance is marked with extensive use of pronouns and repetition of words and phrases.